Peel and cleavage strength tests with adhesive connections in dynamic message signs. (December 2020) - Amatya, Ibin; Seo, Junwon; Letcher, Todd; Ahn, Jin-Hee
Abstract: This paper aims to examine the mechanical properties of the adhesive focusing on peel strength and cleavage strength for varying environmental and geometrical conditions. To that end, peel and cleavage specimens with variations in width were fabricated and examined according to American Society for Testing and Materials (ASTM) after conditioning them in different environmental conditions, including temperature (20 °C, 52.5 °C, and 85 °C) and humidity (48%, 71, 5%, and 95%). The specimens were conditioned in the temperature-humidity controlled chamber for at least 96 h for moisture saturation at each humidity level. The effect of temperature, humidity, and width on peel and cleavage strengths were graphically and statistically examined by analyzing the testing data. As part of the statistical analysis, regression models, encompassing multiple linear regression (MLR) and response surface metamodels (RSM), were established to predict the peel and cleavage strengths. Through evaluation of R-squared values and graphs of the predicted values against the testing data, it was found that the RSM was more accurate than MLR. Key results indicated that the peel strength of tested adhesive specimens was increased with the increment in humidity up to 30.1% and was decreased by the maximum reduction of 28.2% with increment in specimen's width, while the cleavage strength of the tested specimens improved with the peak increment of 27.4% and 28.5% when the temperature and specimen's width was increased, respectively. The cleavage strength, however, was decreased up to 13.7% with the increment in humidity. Findings from 3-D surfaces generated from the RSM to observe the effect of different parameters on the peel and cleavage strength of adhesive joints were in agreement to the testing results. The statistical analysis indicated that the width was a significant parameter affecting the peel strength.